PENGARUH TAX AVOIDANCE, CORPORATE GOVERNANCE DAN DIVIDEND PAYOUT RATIO TERHADAP KINERJA PERUSAHAAN DENGAN STRATEGI BISNIS SEBAGAI VARIABEL MODERASI - Hanny Hanny; Vinola Herawaty; Hasnawati Hasnawati (Jurnal Magister Akuntansi Trisakti, 2018)
The main purpose of this research is to analyze the effect of tax avoidance, corporate governance and dividend payout ratio, with business strategy (as described in typology of Miles and Snow) as moderating variable, on company performance. Company performance is measured by return on assets. In addition, controlling variables used in this reserach are leverage, size and sales growth. Object of this research are manufacturing companies that were listed in Indonesia Stock Exchange during year 2013-2017. Sample determination is performed using purposive sampling method, of which resulted in total samples of 154 companies. The empirical results of this research shows that tax avoidance, corporate governance and dividend payout ratio are positively and significantly related with company performance measured by return on assets. Moderating (interaction) effect of business strategy decreases the association between both tax avoidance and dividend payout ratio, and company performance. Nonetheless, business strategy as moderation variable has no impact on the association between corporate governance and company performance.